Laboratory Activity to Teach about the Proliferation of Salmonella in Vegetables - Massimiliano Marvasi (American Society for Microbiology, 2015)
We designed a three-week laboratory experience that can complement any microbiology teaching laboratory to expand students’ knowledge of the ecology of human enteric pathogens outside of their animal hosts. Through their participation in this laboratory activity, students learned that vegetative and reproductive plant parts could be a natural habitat for enteric bacteria such as non-typhoidal strains of Salmonella enterica. This field was recently brought to the forefront of the scientific community and public interest by outbreaks of human illness linked to the consumption of fresh fruits and vegetables. Students were encouraged to develop their own testable hypotheses to compare proliferation of Salmonella enterica sv Typhimurium LT2 in different vegetables: cherry and regular-size tomatoes, onions, lettuce, and yellow and red bell peppers (Escherichia coli can be substituted for BSL1 laboratories). Upon completion of the laboratory experience, students were able to: 1) Develop testable hypotheses addressing the ability of a human pathogen, Salmonella enterica, to colonize and proliferate in vegetables; 2) Determine that different vegetables support the growth of Salmonella to different extents; 3) Conduct statistical analysis and identify any significant differences. The teaching-learning process was assessed with a pre-/posttest, with an average increase in content understanding from ~15% to 85%. We also measured students’ proficiency while conducting specific technical tasks, revealing no major difficulties while conducting the experiments. Students indicated satisfaction with the organization and content of the practices. All of the students (100%) agreed that the exercises improved their knowledge of this subject.